2022
DOI: 10.1177/03000605221076975
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index is associated with Helicobacter pylori infection and increased oxidative DNA damage in an obese population

Abstract: Objective To determine the prevalence of Helicobacter pylori infection in a Saudi Arabian population and its association with the body mass index (BMI) and serum 8-hydroxy deoxyguanine (8-OHdG) levels as biomarker for oxidative stress. Methods This cross-sectional study enrolled patients that had experienced epigastric discomfort or dyspepsia for > 1 month and had undergone diagnostic upper endoscopy. Patients with a body mass index (BMI) ≥30 kg/m2 were defined as obese. The presence of anti- H. pylori anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…The prevalence of H. pylori infections at 53% in our sample of patients with obesity is comparable to the published data of an H. pylori prevalence of around 66-73% in obese patients in Saudi Arabia and higher than the known prevalence in non-obese patients, which ranges between 26% and 50% [42,43]. This indicates a possible link between obesity and H. pylori infections and could explain at least in part the increased risk of gastric cancer in obese patients [44].…”
Section: Discussionsupporting
confidence: 84%
“…The prevalence of H. pylori infections at 53% in our sample of patients with obesity is comparable to the published data of an H. pylori prevalence of around 66-73% in obese patients in Saudi Arabia and higher than the known prevalence in non-obese patients, which ranges between 26% and 50% [42,43]. This indicates a possible link between obesity and H. pylori infections and could explain at least in part the increased risk of gastric cancer in obese patients [44].…”
Section: Discussionsupporting
confidence: 84%
“…8 However, there is another study that shows a positive linear correlation between nutritional status (BMI) and the incidence of H. pylori infection (p 0.0001), where the risk of H. pylori infection is greater in overweight patients. 16 In this study, there was no association between smoking and the incidence of H. pylori infection (p 0.181). Although included in the regression test (p < 0.25), the final analysis results showed no significant OR value.…”
Section: Discussioncontrasting
confidence: 47%
“…[12] Similarly, a cross-sectional study showed that the prevalence of H. pylori infection in obese individuals was higher than that in individuals with low BMI (BMI < 25 kg/m 2 ). [13] A recent meta-analysis showed that the risk of H. pylori infection was positively correlated with the prevalence of obesity. [14] According to the existing evidence, the relationship between H. pylori infection and obesity may involve several mechanisms.…”
Section: Discussionmentioning
confidence: 99%